Fatal Parastrongylus dujardini Infection in Captive Callitrichids. (March 2015) - Graille, M.; Ferté, H.; Petit, T.; Courtois, F. Ollivet; Gauchot, J.-Y.; Nougaillon, J.-L.; Vitaud, C.; Wardzynski, C.; Lemberger, K.
Intravascular nematodes were considered the cause of death of 14 captive callitrichids. All animals were captive born at zoos in France and died with little or no premonitory signs of disease. No consistent gross lesions were observed at necropsy, although in certain cases intracardiac adult parasites were noted. The most significant histologic findings were verminous pneumonia and pulmonary endarteritis. In all cases except one, intravascular adult nematodes were observed with eggs and larvae in the lungs. Adult nematodes were obtained from 8 animals and in all cases were identified as Parastrongylus dujardini . To the authors' knowledge, this is the first report of intravascular angiostrongylosis with primary cardiopulmonary location in callitrichids in France.